Depressive symptoms, social support, cognitive function, and stigma: predictors of resilience in caregivers of children with intellectual disabilities - Tejakum Wattana; Tankumpuan Thitipong; Suksatan Wanich; Saboonma Jirapan; Phetrasuwan Supapak; Rodney Tamar (Sciendo, 2022)
Objective: Family plays an important role in taking care of children with intellectual disabilities (IDs). Resilience supports coping strategies for caregivers with their children caring. However, factors influencing the resilience of caregivers with ID in Thailand are yet to be identified. Therefore, the aim of this study was to identify the predictors of resilience in caregivers of children with moderate to severe ID.